Pengaruh Budaya Korea Pop terhadap Motivasi Belajar Mahasiswa di Universitas Medan Area - Daulay, Nabila Diffa Ananda; Budiman, Zuhdi (Universitas Medan Area, 2025)
This study aims to examine the influence of Korean Pop (K-Pop) culture on the learning motivation of students at Medan Area University. The focus is on how students’ engagement with K-Pop—through music, idols, and social media—affects their enthusiasm for academic learning. The study applies theories of learning motivation and popular culture engagement. A quantitative approach was used, involving 80 K-Pop fan students selected through purposive sampling. Data were collected via online questionnaires utilizing the K-Pop Culture Scale and the Learning Motivation Scale, then analyzed using simple linear regression. The findings indicate a significant positive influence of K-Pop culture on learning motivation, with a contribution rate of 99.60%. However, excessive involvement in K-Pop-related activities may negatively impact academic focus. Therefore, students are encouraged to manage their engagement wisely so that popular culture can serve as a constructive source of inspiration in their educational journey.